Determining the Safety Performance of Mining Contractors through the Implementation of a Mining Safety Management System - Supardi, Supardi (Greenation Research & Yayasan Global Resarch National, 2025)
The implementation of safety management systems in the mineral and coal mining sector in Indonesia is still not optimal. This study was conducted to analyze how the implementation of safety management systems consisting of planning, organization and personnel, implementation, evaluation and follow-up, and management review affects safety performance in companies. In this study, data was obtained by distributing questionnaires to supervisors, drivers, and heavy equipment operators using simple random sampling techniques, involving a total of 130 respondents, with data analysis using a path analysis model approach. The results of the study indicate that the planning of the safety management system, organization and personnel, implementation of safety programs, evaluation and follow-up, and management review have a significant effect on the achievement of safety performance.